Fitness, Balance Efficacy, and Postural Control in Community-Dwelling Older Adults. (11th February 2016) - Lee, Anna; Biggan, John R.; Ray, Christopher
Age-related declines in postural control and physical fitness are strong risk factors for falls in older adults. Balance efficacy has been utilized to identify poor postural control, reduced physical function, and fall risk. However, it is not clear as to whether balance efficacy is truly a better predictor of functional fitness outcomes or postural control. Distinguishing these associations is an important step in the future derivation of physiotherapeutic programming to remediate acute and chronic decline. Therefore, the purpose of this cross-sectional study was to partition which measures are more associated with balance efficacy, fitness, or postural control. One hundred eleven community-dwelling older adults participated and were asked to complete the Balance Efficacy Scale (BES), a functional fitness measure (the Senior Fitness Test [SFT]), and a measure of postural control (the Sensory Organization Test [SOT]).We found that the SFT was more significantly associated with balance efficacy ( R 2 = .37) than the SOT ( R 2 = .08) in older adults. Overall, aerobic endurance, functional mobility in the SFT, and the vestibular score on the SOT were significantly associated with balance efficacy. We concluded that clinicians utilizing the BES as a preliminary screen should recommend physiotherapy follow-up activities that build endurance (walking), lower extremity functional mobility (sit-to-stand), and vestibular function (head movement while walking). Understanding the links between a preliminary screening tool and the physiological needs of the patient will allow for targeted activities to be prescribed.